Highly efficient gold(I)-catalyzed Overman rearrangement in water - Xing, Dong; Yang, Dan (Beilstein Journal of Organic Chemistry, 2011)
A highly efficient gold(I)-catalyzed Overman rearrangement of allylic trichloroacetimidates to allylic trichloroacetamides in water is reported. With this environmentally benign and scalable protocol, a series of C3-alkyl substituted allylic trichloroacetamides were synthesized in good to high yields.
Keywords: allylic trichloroacetamides; allylic trichloroacetimidate; gold(I) chloride; Overman rearrangement; water